Corporate Community Involvement: An Evaluation of the Strategic Approach - Waritimi, Ekpobomene (2006)
ABSRTACT This research evaluates the strategic approach to corporate community involvement being increasingly adopted by businesses in recent times, with the aim of highlighting the implications for the different actors involved. The study is linked to an internship with Three Hands, a broker firm. In order to achieve the principal aim of the study, three corporate community involvement programmes organized and facilitated by Three Hands, and in which two for-profit organizations and one government agency, and three charity organizations participated are evaluated. The findings of the research are based on qualitative primary data derived from semi-structured in-depth interviews with the commissioners of Three Hands CCI programmes, managers of the charity organizations; and open and closed ended questionnaire prepared for employees who participated in the programmes. The findings are discussed in the light of pertinent literature and conclusions drawn. Having evaluated the strategic approach to corporate community involvement, the conclusion of the research considers a number of implications of this approach to some important actors. The most pertinent implication is that, business organizations are better able to focus their resources where they can make the most impact. In order to achieve this, however, businesses are forging strategic alliances with non-profit organizations, whose objectives or values align somewhat with theirs. The 'under side' of this is that non-profit organizations that do not quite 'fit', stand to miss out on much needed business support.